Spiro‐2‐oxindoles via 1,3‐dipolar cycloadditions. A decade update - Molteni, Giorgio; Silvani, Alessandra (European journal of organic chemistry, 2021)
The great variety of spirooxindole three‐dimensional scaffolds encompasses relevant bioactive natural alkaloids as well as useful therapeutic agents. In view of the challenging features of the spirooxindole skeletons and their desirable properties, several synthetic routes have been devoted to their preparation. Because of the variety of both 1,3‐dipolar species and 2‐oxindoles bearing a C=X double bond (X=C<, N−, O) in the 3‐position, a prominent role relies upon a 1,3‐dipolar cycloaddition as the key step of the whole synthetic sequence. The present paper aims to discuss the developments in the field of spirooxindole synthesis via a 1,3‐dipolar cycloaddition occurred in the 2011–2020 decade. The literature data on this subject are reviewed in a systematic way according to the type of the 1,3‐dipole and the oxindole dipolarophile. The reactivity of 2‐oxindoles bearing a C=X double bond (X=C<, N−, O) in the 3‐position towards a variety of 1,3‐dipolar species has been reviewed in a systematic way according to the type of the 1,3‐dipole, the 2‐oxindole dipolarophile, and the racemic or asymmetric nature of the cycloaddition. Because of the great variety of the resulting spiro‐2‐oxindole skeletons, the developments occurred in the 2010–2020 decade were taken into account.